Narratives of migration and diaspora in contemporary African fiction - Ndaka, Felix Mutunga (My University, 2018)
This study is concerned with contemporary African literature's representation of African migrations and diasporas in the West. The study seeks to grapple with how contemporary African mobilities transform and configure gendered, racial, familial and national relations. Through the use of the novel genre, the study holds that contemporary African writer's representation of experiences of migration and diaspora give us fresh lenses with which to revisit and complicate debates on cultural and intellectual productions in the context of North/South encounters, nation, home and belonging, gendered experiences of mobility and inter- and intraracial relations. The novels under study – No Violet Bulawayo's We Need New Names (2013); Chimamanda Ngozi Adichie's Americanah (2013); Teju Cole's Open City (2011); Dinaw Mengestu's The Beautiful Things That Heaven Bears (2007), and How To Read The Air (2010); Sefi Atta's Everything Good Will Come (2005); and Alain Mabanckou's Blue White Red: A Novel (1998) – portray mobile African characters within local and global contexts and grapple with what it means to be African in a world defined by migration and globalisation, and how being African shapes one's experience of these worlds. The study situates itself critically against triumphant discourses of migration and globalisation by examining postcolonial African subjects whose experiences of migration and global contacts are often framed through the lens of race, gender, class and national dystopias. Through an examination of characters – women, children, marginal African masculinities, ethnic and classed mobilities – who navigate their contacts with the world in varying degrees of vulnerability, the study complicates celebratory and homogenising discourses of global modernity. This study argues that the focalisation on African experiences and perspectives of modernity provide a radical counter-gaze that challenges western discursive control as well as causing epistemic incoherence and disarticulation through diversifying ways of being and knowing. Ultimately, the study's critique of the author's engagement with hegemonic forms enables ideological projects that not only disrupt socio-political and economic hierarchies but also imagine new ethical horizons of human relations
A thesis submitted to the Faculty of Humanities and Social Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy.